An in vivo evaluation of cerebral cortical amyloid with [18F]flutemetamol using positron emission tomography compared with parietal biopsy samples in living normal pressure hydrocephalus patients. - Wong, Dean F; Moghekar, Abhay R; Rigamonti, Daniele; Brasic, James R; Rousset, Olivier; Willis, William; Buckley, Chris; Smith, Adrian; Gok, Beril; Sherwin, Paul; Grachev, Igor D; Brašić, James R (Molecular Imaging & Biology, 2013)
Purpose: The primary objectives of this study were to assess the safety of [(18)F]flutemetamol injection and determine the level of association between the quantitative estimates of brain uptake of [(18)F]flutemetamol and the quantitative immunohistochemical (IHC) estimates of amyloid levels in cerebral cortex biopsies obtained during shunt placement in patients with normal pressure hydrocephalus (NPH).Procedures: Parietal lobe biopsies were obtained from 12 subjects (mean (SD), 71 (8.1) years), during shunt placement for NPH. Shunt procedures and biopsies were performed within 8 weeks after the positron emission tomography (PET) imaging, and followed by a computed tomography scan. The quantitative estimates of the brain uptake of [(18)F]flutemetamol (standard uptake value ratios (SUVRs)) from the biopsy site, contralateral to the biopsy site, and composite were made from the analysis of PET images. The quantitative IHC levels of amyloid load were estimated using a monoclonal antiamyloid β antibody, 4 G8 (in percent area), as the standard of truth (N = 8, of which 5 had full histopathology staining). The primary analysis determined the level of association between the SUVR (with cerebellum as the reference region) from the biopsy site, and the level of amyloid was determined from IHC estimates of amyloid in the biopsy sample.Results: [(18)F]Flutemetamol injection was found to be well tolerated. The biopsied area well represented the amyloid deposition throughout the cortex in this small sample. The biopsy site SUVR was significantly correlated with the biopsy specimen amyloid β level (expressed as percent of biopsy specimen area staining with 4 G8). The full model was significant (p = 0.0174). In the secondary efficacy analyses, contralateral (to biopsy site) and composite SUVR values correlated significantly with the percent of biopsy specimen staining for amyloid β based on 4 G8. Blinded visual [(18)F]flutemetamol image interpretations showed a sensitivity of 100 % and a specificity of 100 % with pathology reads staining for amyloid plaque with Bielschowsky and thioflavin S and overall pathology read. The results of the blinded reader agreement for [(18)F]flutemetamol PET showed full agreement among three readers.Conclusions: PET imaging of NPH patients following the administration of [(18)F]flutemetamol injection was highly correlated with the presence of fibrillar amyloid β in subsequent cortical biopsy samples in this small sample. Administration of [(18)F]flutemetamol injection was well tolerated.